How Do Russia's Regions Adjust to External Shocks? Evidence from the Republic of Tatarstan. Issue 4 (2nd September 2020) - Yakovlev, Andrei; Freinkman, Lev; Makarov, Sergey; Pogodaev, Victor
Abstract : Since 2008, tighter budget constraints have forced the Russian federal government to adjust the system governing its relations with the regions. This paper argues that more advanced Russian regions have the potential to develop a constructive response to the recent deterioration in their operational environment. This argument is based on an analysis of the experiences of coping with the external shocks that have occurred over the last 25 years in the Republic of Tatarstan. The paper identifies key factors that have helped the republic successfully tackle previous shocks, such as elite cohesion and internal consensus regarding republican developmental priorities.